Advances in Murine Models of Diabetic Nephropathy - Li-li Kong; Hao Wu; Wen-peng Cui; Wen-hua Zhou; Ping Luo; Jing Sun; Hang Yuan; Li-ning Miao (Journal of Diabetes Research)
Diabetic nephropathy (DN) is one of the microvascular complications of both type 1 and type 2 diabetes, which is also associated with a poor life expectancy of diabetic patients. However, the pathogenesis of DN is still unclear. Thus, it is of great use to establish appropriate animal models of DN for doing research on pathogenesis and developing novel therapeutic strategies. Although a large number of murine models of DN including artificially induced, spontaneous, and genetically engineered (knockout and transgenic) animal models have been developed, none of them develops renal changes sufficiently reflecting those seen in humans. Here we review the identified murine models of DN from the aspects of genetic background, type of diabetes, method of induction, gene deficiency, animal age and gender, kidney histopathology, and phenotypic alterations in the hope of enhancing our comprehension of genetic susceptibility and molecular mechanisms responsible for this disease and providing new clues as to how to choose appropriate animal models of DN.